2016
DOI: 10.3390/cancers8070067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Intracranial Meningiomas with Emphasis on Canonical Wnt Signalling

Abstract: Research over the last decade recognized the importance of novel molecular pathways in pathogenesis of intracranial meningiomas. In this review, we focus on human brain tumours meningiomas and the involvement of Wnt signalling pathway genes and proteins in this common brain tumour, describing their known functional effects. Meningiomas originate from the meningeal layers of the brain and the spinal cord. Most meningiomas have benign clinical behaviour and are classified as grade I by World Health Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 121 publications
1
40
1
Order By: Relevance
“…Several risk factors for meningiomas have been reported, with ionizing radiation, hypertension, and female sex hormones, showing a possible positive correlation. Much is known about the genetics of meningiomas as well. The effects of various aspects of the metabolic syndrome, primarily glucose metabolism and diabetes, have also been investigated fairly extensively in relation to meningioma risk .…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for meningiomas have been reported, with ionizing radiation, hypertension, and female sex hormones, showing a possible positive correlation. Much is known about the genetics of meningiomas as well. The effects of various aspects of the metabolic syndrome, primarily glucose metabolism and diabetes, have also been investigated fairly extensively in relation to meningioma risk .…”
Section: Discussionmentioning
confidence: 99%
“…The most common chromosomal abnormality in meningioma is in chromosome 22, observed in 40–70% of grade I meningioma. Beyond the loss of chromosome 22, few other chromosomal abnormalities have been observed in benign meningioma ( 10 ). In an analysis of chromosome 22 in 44 sporadic meningiomas, researchers found that in 43 cases, all or part of the chromosome had been deleted, the majority of deletions occurring in the neurofibromatosis type 2 (NF2) region, suggesting that the mutation on NF2 leads to the occurrence of meningioma ( 11 ).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…E-cadherin (encoded by CDH1 at 16q22.1) is a calcium-dependent adhesion molecule, mediating their interaction with epithelial cells ( 40 ). It relies on β-catenin to play a role in cell adhesion, which is considered an indirect regulator of the Wnt signaling pathway ( 10 ). E-cadherin and β-catenin comprise the E-cadherin/catenin complex that regulates cell adhesion and maintains cell polarity and stability ( 40 ).…”
Section: Molecular Mechanisms Of Change In Biological Behaviormentioning
confidence: 99%
“…Meningioma was not an exception; in the last two-decade several papers were published regarding methods and reviews of the molecular biological profile of meningiomas [2,4,5,22,23,33,38,43,47,49]. The efforts of some of these studies helped in identifying unique molecular expression correlated with the WHO grades.…”
Section: Introductionmentioning
confidence: 99%